Silencing of an Ubiquitin Ligase Increases Grain Width and Weight in indica Rice - Verma, Ankit; Prakash, Geeta; Ranjan, Rajeev; Tyagi, Akhilesh K.; Agarwal, Pinky (Frontiers in Genetics, 2021)
Many quantitative trait loci (QTLs) have been identified by molecular genetic studies which control grain size by regulating grain width, length and thickness. Grain width 2 (GW2) is one such QTL that codes for a RING-type E3 ubiquitin ligase and increases grain size by regulating grain width through ubiquitin-mediated degradation of an unknown substrate. A natural variation (SNP at 346th position) in the functional domain coding region of OsGW2 in japonica rice genotypes has been shown to cause an increase in grain width/weight in rice. However, this variation is absent in indica rice genotypes. In this study, we report that reduced expression of OsGW2 can alter grain size, even though natural sequence variation is not responsible for increased grain size in indica rice genotypes. OsGW2 shows higher expression in seed development stages and the protein localizes to the nucleus and cytoplasm. Down regulation of OsGW2 by RNAi technology results in wider and heavier grains. Microscopic observation of grain morphology suggests that OsGW2 determines grain size by influencing both cell expansion and cell proliferation in spikelet hull. Using transcriptome analysis, up-regulated genes related to grain size regulation have been identified among 1426 differentially expressed genes in an OsGW2_RNAi transgenic line. These results reveal that OsGW2 is a suppressor of grain size in indica rice and affects both cell number and cell size in spikelet hull.